Market Reaction to Modified Audit Opinions: A Systematic Literature Review in Both Developed and Developing Countries - Amine El Badlaoui; Mariam Cherqaoui; Issam Er-Rami (Asian Academy of Management Journal of Accounting and Finance, 2023)
The purpose of this paper is to review the empirical literature on value relevance of audit reports by providing current evidence on the market reaction to modified audit opinions (MAOs). This study is motivated by the argument that recent research has resolved the research designs problems raised by the pre-2010 studies that resulted in unmitigated and contradictory results. We adopt a systematic literature review based on the guidelines presented by Kitchenham et al. to review papers published between 2010 and 2020. The main findings of our review show sufficient evidence that MAOs are indeed useful to investors in making decisions in developed countries, which is evidenced by the fact that the MAOs have a negative effect on the share prices of companies. In contrast, evidence from studies conducted in developing countries shows null market reaction to MAOs, with the exception of the Chinese market, which shows a significant reaction. The methodological limitations and alternative causes behind the null market reaction to MAOs of studies conducted in developing countries are discussed in this paper.